Model Cooperative Integrated Reading and Composition dalam Literasi Membaca di Sekolah Dasar - Nursamsi, Nursamsi; Rustan, Edhy; Mirnawati, Mirnawati (South Sulawesi Education Development, 2024)
This research aims to describe the planning, implementation and evaluation of the CIRC learning model on reading literacy of grade III students at SDN 41 Batu Putih. Descriptive qualitative research method was used with data collection techniques through observation, interviews and documentation. The results show that teachers make planning adjustments to the conditions of students and teaching materials. The implementation of the CIRC learning model focuses on differentiated learning, according to students' learning needs. Evaluation shows that the CIRC learning model has been implemented effectively according to the needs of learners.